Atelier sur la gestion de la faune sur les concessions de l'exploitation forestiere d' Afrique centrale - Tutin, C.; Nasi, Robert (2001)
This article is a summary of a Workshop on Wildlife Management in Logging Concessions in Central Africa, La Lupe, Gabon, November 2000. The workshop was unique in that it brought together field-based representatives of logging companies, conservation NGOs and government ministries to discuss practical options for reducing the impact of timber exploitation on wildlife within the forests of Central Africa. This reflects a change in the private sectors concern for consumer attitudes and the risk of brand name black-listing, and the NGO sectors increasing willingness to engage the private sector even if it risks their being accused of green washing logging companies. Preliminary findings from the pilot projects indicate that loggers are willing to reduce the impact of timber exploitation on wildlife within concessions and that collaboration between the private sector and conservation NGOs is possible. Practical options do exist for reducing the impact of timber exploitation on wildlife.